PENGARUH PROFITABILITAS, LIKUIDITAS, DAN STRUKTUR AKTIVA TERHADAP PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PADA PERIODE 2017-2019 - Mettalia Chandra Tjan; Elizabeth Sugiarto Dermawan (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this study was analyze and obtain empirical evidence regarding the effect of profitability, liquidity, and tangibility assets on capital structure. This research was conducted using a purposive sampling method with a total sampel of 214 data from manufacturing companies listed on Indonesia Stock Exchange with an observation period of 3 years, 2017-2019. This research was conducted using secondary data obtained from the financial statements cintained on the website www.idx.com. The results obtained from the study concluded that the profitability variables has a positif and not significant effect on capital structure, while the liquidity variables and tangibility assets variables have a negatif and significant effect on capital structure.